👤

Learning Task 1 .Simplily by writing in exponential form. the first example is done for you. 1. (2) (2") - 2x 2 * 2 * 2 x 2 = 2 = 32 6.(-4) (-4) (-4) (-4)= 2. (x) (x) 7. (xy)" 3. (3) (3) 8. (x) (x4) = 4. (2") (2") = 9. (-ab) = 5. (3a) (3a) (3a) (3a) = 10. (55)6 = ​

Learning Task 1 Simplily By Writing In Exponential Form The First Example Is Done For You 1 2 2 2x 2 2 2 X 2 2 32 64 4 4 4 2 X X 7 Xy 3 3 3 8 X X4 4 2 2 9 Ab 5 class=

Sagot :

Answer:

Simplify by writing in exponential form

6

1).2

4

2).(3a)

5

3.(-4)

Step-by-step explanation:

Write the expanted form

1.(2x)(2x)(2x)(2x)

2.(xy) (xy) (xy) (xy) (xy) (xy) (xy)

3.(-ab) (-ab) (-ab) (-ab) (-ab) (-ab)